Official ceremony for Memorandum Of Understanding (MoU) between Universiti Teknologi Mara (UiTM) and Iowa State University, United States Of America / Nur Hidayah Che Ahmat - Che Ahmat, Nur Hidayah (2022)
An official ceremony for Memorandum of Understanding (MoU) between Universiti Teknologi MARA (UiTM) and Iowa State University, United States of America, was done on 17th January 2022 (10:00 PM, Malaysia time / 8:00 AM, Central Iowa time). Iowa State University was represented by Professor Dr. Eulanda Sanders, Department Chair of Apparel, Events, and Hospitality Management, and witnessed by Professor Dr. Susan Wohlsdorf Arendt, University Faculty Fellow for Online Learning, and Associate Professor Dr. Lee SoJung, Director of Graduate Education for Hospitality Management. UiTM Cawangan Pulau Pinang was represented by Professor Ts. Dr. Salmiah Kasolang, Rector UiTMCPP, and witnessed by Associate Professor Ir. Dr. Ahmad Rashidy Razali, Deputy Rector of Academic and International Linkages for UiTMCPP. Dr. Nur'Hidayah Che Ahmat, a Senior Lecturer at the Faculty of Hotel and Tourism Management, initiated this MoU with her team members (Dr. Anderson Ngelambong, Dr. Wan Rusni Wan Ismail, Dr. Rafidah Aida Ramli, Associate Professor Ts. Dr. Norfezah Md Nor). Dr. Nur'Hidayah is an Iowa State University alumnus (#cycloneseverywhere). Iowa State University, founded in 1858, is a public, land-grant university located in Ames, Iowa, United States of America. The university offers undergraduate and graduate programmes in various disciplines, with more than ten schools and colleges offering at least 100 majors, including events and hospitality management. The university recorded more than 30,000 student enrolments in Fall 2021. The university's mission is to "Create, share, and apply knowledge to make Iowa and the world a better place." The signing of this MoU will provide many collaboration opportunities for both institutions, including the faculty and student mobility programmes, exchange of information about developments in teaching, student development, and research innovation and commercialization. Additionally, both institutions will collaborate in organizing conferences and symposia. Overall, this MoU will bridge academicians and students from UiTM and Iowa State University. It is hoped that this MoU will boost UiTM's visibility towards becoming a Globally Renowned University.